Luther's Schem Hamphoras. Issue 2 (June 2017) - Schramm, Brooks
Abstract: This article provides a concise summary of Luther's anti‐Jewish treatise, On the Schem Hamphoras and On the Lineage of Christ (March 1543) and describes its purpose, interworkings, and scatological rhetoric. The treatise is interpreted as Luther's defense of the Second Commandment over against Jewish superstitions regarding the name of God; his attempt to undermine the credibility of the rabbis and their influence on the Christian Hebraists; and his further strengthening of his platform for the expulsion of the Jews as initially articulated in On the Jews and Their Lies (January 1543).